The aging-disease false dichotomy: understanding senescence as pathology - Gems, David (Frontiers in Genetics, 2015)
From a biological perspective aging (senescence) appears to be a form of complex disease syndrome, though this is not the traditional view. This essay aims to foster a realistic understanding of aging by scrutinizing ideas old and new. The conceptual division between aging-related diseases and an underlying, non-pathological aging process underpins various erroneous traditional ideas about aging. Among biogerontologists, another likely error involves the aspiration to treat the entire aging process, which recent advances suggest is somewhat utopian. It also risks neglecting a more modest but realizable goal: to develop preventative treatments that partially protect against aging.